-5y(y-5)=-3y+45

Simple and best practice solution for -5y(y-5)=-3y+45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5y(y-5)=-3y+45 equation:



-5y(y-5)=-3y+45
We move all terms to the left:
-5y(y-5)-(-3y+45)=0
We multiply parentheses
-5y^2+25y-(-3y+45)=0
We get rid of parentheses
-5y^2+25y+3y-45=0
We add all the numbers together, and all the variables
-5y^2+28y-45=0
a = -5; b = 28; c = -45;
Δ = b2-4ac
Δ = 282-4·(-5)·(-45)
Δ = -116
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 8-2(12+12)=5-2x-13 | | 5-4|-3x|=-36 | | r-5=43 | | -4b=-8-6b^2+4b | | c+25=671 | | 4+9.75x=0.25x+ | | 5+5(n-1)=19 | | -(x+3)+4x=6 | | n+(n+1)+(n+2)+(n+3)+(n+4)=55 | | 10+7.5n=8+7.9n | | 128=k-39 | | h+94=891 | | (2x+7)=65 | | v+9-48=1 | | h+94=894 | | –17+15z=13z+19 | | 2n+8=60 | | 459=27g | | n+(n+1)+(2(n+2)+2(n+3)+55)=3(n+4) | | 634=p+551 | | H=210+33x | | 162+24.50x=4.25 | | -x2+2x=3 | | 4c+2c=4 | | 70x-60=-20x-42 | | r-705=-325 | | -2x/3-3=3 | | w+-66=-95 | | 10w=-8-8w | | 3x(1-x)+12=-3x(x-3) | | -9(5-2)=4(t-15) | | n+(n+1)+2((n+2)+(n+3)+55)=3(n+4) |

Equations solver categories